Lichen recolonization in the city of Toruń - Adamska, Edyta (Ecological Questions, 2013)
Together with the decreasing pollution load in the atmosphere, particularly with sulphur oxides, one can observe inhibition of the process of lichens’ biota impoverishment in areas with the increased anthropopressure. Since the end of the 1970s, in most of the cities of Western Europe, the process of recolonization by lichens has been observed. Recently, this phenomenon has been described also in Poland. As a consequence of lichenological researches, carried out in the city of Toruń between 2001 and 2010, as well as based on the literature data, one can confirm the first symptoms of the process of recolonization by these organisms within the city area. In this paper, the most spectacular examples are presented in order to illustrate the early process of recolonization by epiphytic lichens in the city of Toruń during the last 60 years.